Ilmu Balaghah dan hubungannya dengan kemukjizatan Al-Qur’an: Keindahan bahasa Arab dalam Al-Qur’an - Khotimah, Khusnul (Maliki Interdisciplinary Journal, 2024)
This abstract discusses the science of balaghah, which is an in-depth study of the beauty and superiority of the Arabic language, and its relationship to the miracles of the Koran. The science of balaghah allows us to understand how beautiful the language structure of the Qur’an is, which not only conveys meaning clearly but also with a unique and amazing language style. The Qur’an is recognized by many scholars as a linguistic miracle because of its ability to express profound concepts in words filled with beauty, precision, and order. The use of various language styles such as majaz, balaaghah, and qinaayah in the Qur’an shows extraordinary skill in arranging words to influence the hearts and minds of the readers. This research explores how the science of balaghah allows us to appreciate the uniqueness of the Al-Qur’an as a literary work and also as a divine revelation. .By understanding the principles of balaghah, such as mujmal and mubayyan, as well as majaz such as tamsil and isti’ara, we can see how the Qur’an is not only a spiritual guide but also a model of excellence in the use of language. This study highlights how important the science of balaghah is in appreciating the miracles of the Qur’an, and how it can deepen our understanding of the messages contained therein. In conclusion, the science of balaghah provides deep insight into the richness of the language of the Qur’an and confirms that its beauty is not only in terms of the meaning of the words but also in the structure of the language which is very beautifully structured.